Plasma N-terminal pro-B-type natriuretic peptide and urinary aldosterone-to-creatinine ratio in healthy Chihuahuas - Alberto Galizzi; Greta Dossi; Paola Pocar; Vitaliano Borromeo; Chiara Locatelli (BMC Veterinary Research, 2024)
Abstract Background Chihuahua represents an increasingly widespread breed predisposed to cardiac disease. N-terminal pro-B-type natriuretic peptide (NT-proBNP) might be a useful point-of-care biomarker for dogs suspected of having heart disease, but breed differences have been reported. The urinary aldosterone-to-creatinine ratio (UAldo: C) appears to be a good indicator of renin-angiotensin-aldosterone system activity in dogs, but Chihuahuas showed significantly higher UAldo: C than other breeds. The objective of this study was to assess preliminary breed-specific reference intervals for NT-proBNP and UAldo: C in healthy Chihuahuas and evaluate sex differences in these parameters. Results Forty-three healthy Chihuahuas dogs were enrolled. The median NT-proBNP was 347 (125–515) pmol/L, and the median UAldo: C was 2.59 (1.57–4.61) µg/g. The NT-proBNP reference interval was 125 (90% CI 125–125) – 2121.4 (90% CI 941.6–2248) pmol/L. 91% of the Chihuahuas were below the nonbreed-specific cut-off (900 pmol/L). The UAldo: C reference interval was 0.6 (90% CI 0.5–0.9) – 16.8 (90% CI 10.9–27.4) µg/g. No significant sex differences in NT-proBNP or UAldo: C were found. Conclusions The median value, interindividual coefficient of variation and reference interval of NT-proBNP were in line with those reported for other small breeds. In contrast to previous studies, no sex differences in NT-proBNP were detected. As previously suggested, Chihuahuas seem to be characterized by higher values of UAldo: C than other breeds.